The preparation and characterization of multi-component systems in drug pre-formulation - Vicatos, Alexios Ivan (Department of Chemistry, 2019)
The supramolecular derivatisation, via co-crystallization and cyclodextrin (CD) inclusion of three active pharmaceutical ingredients (APIs), was attempted with the aim of generating new solid forms with potential pharmaceutical application. The APIs under investigation included allopurinol (used for the treatment of gout and kidney stones), 6-thioguanine (used to treat acute myelogenous leukaemia) and valproic acid (for treatment of epilepsy and bipolar disorders). Allopurinol and 6-thioguanine were fairly intractable, yielding very limited results following co-crystallization trials with a series of co-formers. However, a new polymorph of one of the co-formers, namely isonicotinamide, was discovered serendipitously and thoroughly characterized using thermal analysis and single crystal X-ray diffraction. Phase solubility studies with a variety of CDs showed that the poor aqueous solubility of allopurinol and 6-thioguanine was not significantly modified in the presence of CD solutions. However, a more accurate aqueous solubility value for 6-thioguanine was achieved, namely 0.078 ± 0.003 mg.cm-3 at 25 o C. Six new CD complexes of valproic acid (VAL) were isolated by kneading and/or coprecipitation methods and characterized by thermal analysis, powder X-ray diffraction and spectroscopic (1H NMR and FT-IR) techniques. The six CD complexes (with host-guest stoichiometries in parentheses) included -CD·VAL (2:1), -CD·VAL (1:1), -CD·VAL (4:3), DMB·VAL (1:1), TMB·VAL (1:1) and TMA·VAL (1:1). The -CD·VAL, -CD·VAL, and -CD·VAL complexes were assessed for their ability to alter the aqueous solubility of the drug at 23 o C. The SCD/So ratios for these CD complexes (SCD being the solubility of VAL in the form of the CD complex and So the solubility of pure VAL) were 0.39, 0.42 and 0.41 respectively and thus CD complexation reduced the aqueous solubility of valproic acid. Single crystal X-ray structures of four of the CD-valproic acid complexes were determined, those with native CDs featuring fully disordered guest molecules, while those with permethylated -CD and dimethylated -CD revealed the modes of inclusion of the drug unequivocally.